Peningkatan Hasil Belajar Matematika Siswa Melalui Model Discovery Learning Berbantuan Quizizz Kelas II SDN 04 Kota Bengkulu - Kurniawati, Ike; Lusa, Herman; Mabara, Sefbinata (UNIB Press, 2024)
This research aims to improve the mathematics learning outcomes of class II students at SDN 04 Bengkulu City through the application of the Discovery Learning learning model assisted by the Quizizz application. The research method used is classroom action research (PTK) with two cycles, each consisting of planning, implementation, observation and reflection stages. The research subjects were 30 class II students. Data was collected through learning results tests, observation and documentation, then analyzed descriptively. The research results show that the application of the Discovery Learning model assisted by Quizizz can improve students' mathematics learning outcomes. In cycle I, the average student learning outcome score increased from 65 (pre-cycle) to 75, with a learning completion percentage of 70%. In cycle II, the average score increased to 85, with a learning completion percentage reaching 90%. The conclusion of this research is that the Discovery Learning model assisted by Quizizz is effective in improving the mathematics learning outcomes of class II students at SDN 04 Bengkulu City.